Imagens da infância: brincadeira, brinquedo e cultura - Levindo Diniz Carvalho (2007)
In the present work we describe and analyze the repertory of toys and playing activities experienced by Amerindian Pataxó children of the state of Minas Gerais and also by children living in the Taquaril neighborhood of Belo Horizonte. This study intended to comprehend how children from different sociocultural contexts experience the practices of games, including there dynamics and meanings. We also investigated which elements peculiar to the sociocultural milieu arises from this experience, understanding the act of playing as a typical way of the children to comprehend and apprehend the world. The main theoretical references of this work are contemporary studies in the fields of sociology, anthropology, and childhood history, focused mainly on the understanding of the child as a sociohistorical and cultural actor and producer of a unique culture that is built through the interaction with the adult culture. Based on the comprehension of each sociocultural context in which the different observed groups live, we accomplished a sociological investigation of the child daily routines. This was in order to apprehend the repertory of the cultural practices of each group, there interactions and there generation of meanings about there actions. In this study, prominence is given to the different uses of spaces and time in playing in each sociocultural context, and the relationships established, while playing, with the adults and the elements of the adult culture. From the analyzes of relationships between playing activities and toys of different contexts, from the cartography of similarities, specificities, and, specially, from the apprehension of the cultural dimension of this practice, rises singular, universal and seasonal characteristics, that constitute a repertory of toys and playing activities. It is also revealed, in those practices, the conditions of childhood living, as well as cultural belonging and identity traces of each group. In this sense, this work, as long as it searches to understand playing as a child language that denotes signification to the world, contributes to the establishment of a way of seeing the child in her singularity and in the forms she apprehends and relates itself with her pairs and environment. It also contributes to the elaboration of the built images over the multiple childhoods in the contemporaneity.